2008
DOI: 10.1007/s00449-007-0186-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of extracellular psychrophilic alkaline lipase produced by marine Pseudomonas sp. (MSI057)

Abstract: An endosymbiotic Pseudomonas sp. (MSI057), which could produce high yields of lipase, was isolated from marine sponge Dendrilla nigra, collected from the peninsular coast of India. Maximum production of enzyme was obtained in minimal medium supplemented with 1% tributyrin. Catabolite repression was observed when the medium was supplemented with readily available carbon sources. The optimum temperature and pH for the enzyme production was 30 degrees C and 9.0, respectively. The enzyme exhibited maximum activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 43 publications
3
40
1
2
Order By: Relevance
“…Increasing or decreasing the temperature causes a decrease in enzyme units showing that P. putida is a mesophilic bacterium 30°C. Similar results have been shown by Padhiar et al [15] for P. aeruginosa and Kiran et al [16] who found 30°C as the optimum temperature for enzyme production from Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 88%
“…Increasing or decreasing the temperature causes a decrease in enzyme units showing that P. putida is a mesophilic bacterium 30°C. Similar results have been shown by Padhiar et al [15] for P. aeruginosa and Kiran et al [16] who found 30°C as the optimum temperature for enzyme production from Pseudomonas sp.…”
Section: Discussionsupporting
confidence: 88%
“…Aeromonas hydrophila and Pseudomonas sp. MSI057 were isolated from marine environment and marine sponge, respectively (Pemberton et al 1997;Kiran et al 2008). Recently, Janibacter sp.…”
Section: Sources Of Clpsmentioning
confidence: 99%
“…The maximum production of lipase (3.69 U/mL) was obtained at pH of 8.0 (Figure 7). This might be because organism required a slightly basic pH for its metabolic processes as well as for the production of lipases (Kiran et al, 2008). Increase or decrease in pH had negative impact on the production of lipase.…”
Section: Effect Of Ph Of the Medium On Production Of Lipase -mentioning
confidence: 99%